High-barrier waterproof and oil-proof PHA composite film and preparation method thereof, and prepared protective inflatable bubble bag and paper cup

By adopting specific process conditions in PHA casting processing, including drying and hot pressing, a high-barrier, waterproof and oil-resistant PHA composite film is formed, which solves the problem of molecular chain instability of PHA at high temperatures, and achieves better barrier and breakage resistance.

CN119639037APending Publication Date: 2025-03-18DONGGUAN RUIZEARTS NEW MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411501840.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During casting processing, PHA needs to be heated to above 200°C, resulting in unstable molecular chains and prone to fracture, crosslinking or depolymerization, reducing barrier properties and physical properties after film formation.

Method used

By dispersing the PHA particles in the dispersion liquid, a PHA dispersion with a solid content of 60-70%, was formed, and dried at 145-155°C, followed by hot pressing at 175-185°C to form a high barrier, waterproof and oil-resistant PHA composite film.

Benefits of technology

This process makes the PHA composite film have better barrier properties and breakage resistance, reducing damage, oxygen permeability, moisture permeability, oil permeability, etc., and improving its practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102811960000041
    Figure BDA0005102811960000041
  • Figure BDA0005102811960000051
    Figure BDA0005102811960000051
  • Figure BDA0005102811960000052
    Figure BDA0005102811960000052
Patent Text Reader

Abstract

The invention relates to the field of packaging materials, in particular to a high-barrier waterproof and oil-proof PHA composite film, a preparation method of the PHA composite film and a prepared protective inflatable bubble bag and paper cup. Comprising the following steps: dispersing PHA particles in a dispersion liquid to obtain a PHA dispersion with the solid content of 1-3%, and then carrying out vacuum distillation to obtain a PHA dispersion with the solid content of 60-70%; the method comprises the following steps: coating a PHA dispersion with the solid content of 60-70% on a base material, and drying at 145-155 DEG C to form a coating on the base material; and carrying out hot pressing on the surface containing the coating at 175-185 DEG C to obtain the PHA composite film. Through the production process, the obtained PHA dispersion with the solid content of 60-70% is subjected to coating, curing and hot pressing to form a stable PHA layer, so that the obtained PHA composite film has better barrier property and physical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of packaging materials, and more specifically, to a high-barrier, waterproof and oil-proof PHA composite film, a preparation method thereof, and a protective inflatable bubble bag and paper cup obtained therefrom. Background Art

[0002] PHA is extracted from agricultural by-products, food waste and vegetable oils through pretreatment and fermentation. The organic matter is used as the carbon source and energy for microorganisms to produce PHA. The resulting PHA is environmentally friendly and degradable, and has excellent biodegradability, heat resistance, heat sealing, barrier properties and hydrolysis stability. Therefore, it is widely used in green packaging, tableware, cosmetics, fiber fabrics and other high-end application products.

[0003] When PHA is used to produce packaging bags, it needs to be formed into a film through a casting process and then used in the production of packaging bags. During the casting process, PHA needs to be heated to above 200°C to melt it, and then extruded into a sheet or film through a specific mold or equipment, and finally cooled and solidified to obtain the finished product.

[0004] However, PHA will experience significant thermal degradation at a high temperature of 200°C. This is because the molecular chain of PHA becomes unstable at high temperatures and is prone to reactions such as breakage, cross-linking or depolymerization, resulting in reduced physical properties after film formation, and then easy to crack, reducing the barrier properties of PHA after film formation, so further research is needed. Summary of the invention

[0005] In order to further improve the barrier properties of PHA, the present application provides a high-barrier, waterproof and oil-proof PHA composite film and a preparation method thereof, and a prepared protective inflatable bubble bag and paper cup.

[0006] In a first aspect, the present application provides a method for preparing a high barrier, water-proof and oil-proof PHA composite film, comprising the following steps: Dispersing PHA particles in a dispersion liquid to obtain a PHA dispersion having a solid content of 1-3%, and then performing vacuum distillation to obtain a PHA dispersion having a solid content of 60-70%; A PHA dispersion with a solid content of 60-70% is coated on a substrate, and dried at 145-155° C. to form a coating on the substrate; the side containing the coating is hot pressed at 175-185° C. to obtain a PHA composite film.

[0007] In the above scheme, the obtained PHA dispersion with a solid content of 60-70% is semi-solid. At this time, the PHA is still in a particle state and has a certain degree of adhesion. Therefore, when applied, it is easy to adhere to the substrate to form a uniform coating. When it is at 175-185°C, it is easy to perform hot pressing. At this hot pressing temperature, the PHA material is not prone to molecular breakage and reduce its physical properties. At the same time, under this temperature, the PHA can be completely melted and a stable PHA layer can be formed on the substrate. The obtained PHA composite film has both good barrier properties and physical properties. Reduce the occurrence of breakage, oxygen permeability, moisture permeability, oil permeability, etc., and improve its practicality.

[0008] Preferably, the drying time is 35-200s, and the hot pressing pressure is 30-60MPa.

[0009] The above process conditions are the preferred process conditions for this application. The PHA composite film obtained by the process conditions has better barrier properties and tear resistance.

[0010] The barrier properties in this application mainly refer to the properties of oxygen barrier, moisture barrier and oil barrier.

[0011] Preferably, the particle size of the PHA particles is 0.1-5 microns.

[0012] Preferably, the PHA-carboxyl-terminated polycaprolactone composite particles are composed of raw materials in the following weight percentages: PHA 87-93% Carboxyl terminated polycaprolactone 5-10% Hydrogenated Rosin Alcohol 0.2-0.5% The balance is plasticizer and dispersant.

[0013] Hydrogenated rosin alcohol is a compound extracted from rosin and hydrogenated, and has good adhesion. Carboxyl-terminated polycaprolactone is a polycaprolactone derivative with a carboxyl functional group. When hydrogenated rosin alcohol is compounded with carboxyl-terminated polycaprolactone and blended with PHA for modification, with the assistance of a plasticizer and dispersant, the obtained PHA-carboxyl-terminated polycaprolactone composite particles have good adhesion, physical properties, barrier properties and film-forming properties, and the obtained PHA-carboxyl-terminated polycaprolactone composite particles have a low melting point. Therefore, the formed PHA dispersion is easy to adhere to the substrate and is cured to form a stable coating. When hot-pressed at 175-185°C, the PHA-carboxyl-terminated polycaprolactone composite particles can be quickly melted and dispersed, so that a PHA composite film with a stable and uniform film structure is formed after hot pressing.

[0014] When hydrogenated rosin alcohol, carboxyl-terminated polycaprolactone, and a plasticizer dispersant are compounded in the present application and then blended and modified with PHA, the obtained PHA-carboxyl-terminated polycaprolactone composite particles have a lower melting temperature, and the semi-molten PHA dispersion is easily coated on the surface of the substrate to form a PHA coating with uniform thickness. In addition, during the hot pressing process, it can be quickly melted and dispersed to form a uniformly dispersed PHA film, so as to improve the barrier properties of the PHA composite film and obtain better physical properties.

[0015] Preferably, the relative molecular weight of the carboxyl-terminated polycaprolactone is 500-1000.

[0016] The plasticizer dispersant is epoxidized soybean oil and / or methyl palmitoleate.

[0017] Epoxidized soybean oil, soybean oleic acid alkyd resin, and palmitoleic acid methyl ester all play a role in improving toughness and melt fluidity, and play a role in improving fluidity and dispersibility. When using and / or palmitoleic acid methyl ester as a plasticizer and dispersant, the PHA-carboxyl-terminated polycaprolactone complex particles can obtain a lower processing temperature, and the PHA dispersion formed is easy to adhere to the substrate during the dispersion process, and forms a stable coating after solidification, and during the hot pressing treatment, the PHA-carboxyl-terminated polycaprolactone complex particles can be quickly melted and dispersed, thereby forming a uniformly dispersed PHA film layer, and the adhesion to the substrate surface is stable, and it plays a better role in flame retardancy and burst resistance.

[0018] Preferably, the PHA-carboxyl-terminated polycaprolactone composite particles are prepared by the above method: PHA, carboxyl-terminated polycaprolactone, hydrogenated rosin alcohol, and a plasticizer dispersant were weighed according to weight percentage, heated until all melted, and fully mixed, cooled, and crushed to obtain PHA-carboxyl-terminated polycaprolactone composite particles.

[0019] In the above process, hydrogenated rosin alcohol, carboxyl-terminated polycaprolactone and plasticizer dispersant are added to molten PHA to blend and modify PHA, so that the melting point of the PHA-carboxyl-terminated polycaprolactone composite particles is lower than that of PHA, and in the state of PHA dispersion, it is easy to disperse and coat. When hot pressed, it can melt quickly and form a uniform PHA composite film, and has stable adhesion to the substrate, so that the obtained PHA composite film has better barrier properties and physical properties.

[0020] In a second aspect, the present application provides a high-barrier, waterproof and oil-proof PHA composite film, comprising a base layer, at least one side of the base layer being provided with a PHA layer, and the PHA composite film is obtained by a method for preparing a high-barrier, waterproof and oil-proof PHA composite film.

[0021] The PHA composite film of the present application has better barrier properties and tear resistance.

[0022] The third aspect includes a bag body, wherein a filling cavity is arranged inside the bag body, and the characteristics are: the bag body is made of a high-barrier, waterproof and oil-proof PHA composite film, the side containing the PHA layer is the inner side of the bag body, one side edge of the bag body is overlapped and sealed, and the two end edges of the bag body are overlapped and hot-pressed.

[0023] Currently available protective inflatable bubble bags are formed by inflating plastics such as PE and PP, but the above plastics are not environmentally friendly. Some are made by casting PHA materials, but the casting processing temperature needs to be 200°C. At this high temperature, the heat tolerance of PHA is reduced, and the molecular structure will break, which will affect the physical properties and barrier properties of the PHA film, and thus cause the protective inflatable bubble bags to be easily damaged and prone to oxygen permeability.

[0024] The PHA composite film produced by the process of the present application can be heat-sealed at a relatively low temperature, and the processing temperature does not exceed 200°C. Therefore, it is not easy to damage the molecular structure of PHA, and thus has better oxygen barrier, moisture barrier and physical properties. The resulting protective inflatable bubble bag is not easy to break when subjected to pressure, and is used in transportation packaging to resist pressure and oxygen penetration, thereby providing better protection for the packaged products.

[0025] When both sides of the PHA composite film contain PHA layers, the PHA composite film is suitable for the production of large-scale physical protective transportation, such as large household appliances such as refrigerators and washing machines, or large-scale production equipment.

[0026] When one side of the PHA composite film contains a PHA layer, it is suitable for protecting small electronic products, cosmetics, etc.

[0027] In a fourth aspect, the present application provides a paper cup, comprising a cup body and a cup bottom, wherein the cup body and the cup bottom are both made of paper cup paper, and are characterized in that: the paper cup paper comprises a paper layer and at least one layer of PHA composite film, wherein the PHA composite film is a high barrier, waterproof and oil-proof PHA composite film, and the side of the PHA composite film containing the PHA layer is heat-sealed to the paper layer; the inner surface of the cup body contains the PHA layer, and the inner surface of one end face of the cup body is connected to the outer surface of the other end face of the cup body by being rolled and hot-pressed and sealed, and the side of the cup bottom containing the PHA layer is close to the cup body, and the outer edge of the cup bottom is provided with a folded edge, and the folded edge is hot-pressed and sealed to the inner surface of the cup body.

[0028] The PHA composite film prepared by the present application, when used in paper cups, can play a better role in waterproofing and oil-proofing, and reduce the occurrence of water leakage and the like.

[0029] In summary, this application has the following beneficial effects: 1. Through the production process of this application, the obtained PHA dispersion with a solid content of 60-70% has a certain degree of adhesion. When applied, it is easy to adhere to the substrate to form a uniform coating, and after hot pressing, the PHA is completely melted and a stable PHA layer is formed on the substrate, so that the obtained PHA composite film has both better barrier properties and physical properties. Reduce the occurrence of breakage, oxygen permeability, moisture permeability, oil permeability, etc., and improve its practicality.

[0030] 2. After compounding hydrogenated rosin alcohol, carboxyl-terminated polycaprolactone and plasticizer dispersant, they are blended and modified with PHA, so that the obtained PHA-carboxyl-terminated polycaprolactone composite particles have a lower melting temperature, and the semi-molten PHA dispersion is easy to be coated on the surface of the substrate to form a PHA coating with uniform thickness. In addition, during the hot pressing process, it can be quickly melted and dispersed to form a uniformly dispersed PHA film layer, so as to improve the barrier properties of the PHA composite film and obtain better physical properties. DETAILED DESCRIPTION

[0031] The present application is further described in detail below with reference to the embodiments.

[0032] Introduction of some raw materials; Table 1 Introduction of some raw materials Preparation Example of PHA-carboxyl-terminated polycaprolactone composite particles Preparation Example 1 A PHA-carboxyl-terminated polycaprolactone composite particle is prepared by the following method: According to weight percentage, 87% PHA, 10% carboxyl-terminated polycaprolactone, 0.2% hydrogenated rosin alcohol, and 2.7% plasticizer dispersant were weighed and heated to 178° C., at which time PHA was completely melted, and PHA, carboxyl-terminated polycaprolactone, hydrogenated rosin alcohol, and plasticizer dispersant were fully mixed and cooled to 25° C., and then put into a pulverizer for pulverization, and ground to obtain PHA-carboxyl-terminated polycaprolactone composite particles with a particle size of 1 micron.

[0033] The plasticizer and dispersant is epoxidized soybean oil.

[0034] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used is different, as shown in Table 2; Table 2 Raw materials weight percentage (%) of preparation examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 2 is that the dispersing plasticizer is composed of epoxidized soybean oil and methyl palmitoleate in a weight ratio of 1:1.

[0035] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 2 is that the dispersed plasticizer is composed of epoxidized soybean oil and methyl palmitoleate in a weight ratio of 2:1.

[0036] Preparation Comparative Example Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of hydrogenated abietic alcohol is replaced by PHA.

[0037] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of carboxyl-terminated polycaprolactone is replaced by PHA. Example

[0038] Example 1 A high-barrier, waterproof and oil-proof PHA composite film comprises a base layer, one side of the base layer is provided with a PHA layer, and the PHA composite film is obtained by the following method: The dispersion is obtained by uniformly mixing water, sodium hydroxymethyl cellulose and PVA in a weight ratio of 1000:1:1.

[0039] Dispersing PHA particles in the dispersion to obtain a PHA dispersion with a solid content of 1%, and then performing vacuum distillation at a distillation temperature of 120° C. with a vacuum gauge showing -0.1 MPa to obtain a PHA dispersion with a solid content of 60%; A PHA dispersion with a solid content of 60% is coated on one side of a substrate, and dried at 145° C. for 200 seconds to form a coating on one side of the substrate; the coating is hot-pressed at 175° C. for 1 second with a hot-pressing pressure of 30 MPa to form a uniform PHA film layer on one side of the substrate to obtain a PHA composite film.

[0040] In the above, the thickness of the PHA film layer is 0.01 mm, the base layer is 30 gsm wood pulp paper; and the particle size of the PHA particles is 5 microns.

[0041] Example 2 The difference between Example 2 and Example 1 is that: PHA layers are provided on both sides of the base layer, and the PHA composite film is obtained by the following method: Dispersing PHA particles with a particle size of 5 microns in the dispersion liquid to obtain a PHA dispersion with a solid content of 1%, and then performing vacuum distillation at a distillation temperature of 120° C., with a vacuum gauge showing -0.1 MPa, to obtain a PHA dispersion with a solid content of 65%; A PHA dispersion with a solid content of 65% is coated on both sides of a substrate and dried at 150°C for 120s to form a coating on both sides of the substrate; a double-sided hot pressing method is used to hot press the coating at 180°C for 1s with a hot pressing pressure of 40MPa to form a uniform PHA film layer on both sides of the substrate, and the thickness of each PHA film layer is 0.01mm, thereby obtaining a PHA composite film.

[0042] Example 3 The difference between Example 3 and Example 2 is that the process conditions are different, as follows: Dispersing PHA particles in the dispersion to obtain a PHA dispersion with a solid content of 3%, and then performing vacuum distillation at a distillation temperature of 120° C. with a vacuum gauge showing -0.1 MPa to obtain a PHA dispersion with a solid content of 70%; A PHA dispersion with a solid content of 70% is coated on both sides of a substrate and dried at 155°C for 35 seconds to form a coating on both sides of the substrate; a double-sided hot pressing method is used to hot press the coating at 185°C for 1 second with a hot pressing pressure of 60 MPa to form a uniform PHA film layer on both sides of the substrate to obtain a PHA composite film.

[0043] Example 4 The difference between Example 4 and Example 3 is that the particle size of the PHA particles is 0.1 micrometer.

[0044] Example 5 The difference between Example 5 and Example 3 is that the particle size of the PHA particles is 1 micron.

[0045] Example 6 The difference between Example 6 and Example 5 is that the PHA particles are the PHA-carboxyl-terminated polycaprolactone composite particles obtained in Preparation Example 1.

[0046] Examples 7-12 The difference between Examples 7-12 and Example 6 is that the sources of the PHA-carboxyl-terminated polycaprolactone composite particles are different, as shown in Table 3; Table 3 Sources of PHA-carboxyl-terminated polycaprolactone composite particles of Examples 6-10 Example PHA-carboxyl-terminated polycaprolactone composite particles Example 6 Preparation Example 1 Example 7 Preparation Example 2 Example 8 Preparation Example 3 Example 9 Preparation Example 4 Example 10 Preparation Example 5 Embodiment 11 Preparation Comparative Example 1 Example 12 Preparation Comparative Example 2 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that a casting process is adopted; the details are as follows: The PHA was heated to 200°C, then coated on the paper surface, and cooled to 25°C to form a PHA layer on both sides of the substrate to obtain a PHA composite film.

[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that there is no hot pressing process; the specific steps are as follows: Dispersing PHA particles in the dispersion to obtain a PHA dispersion with a solid content of 1%, and then performing vacuum distillation at a distillation temperature of 120° C. with a vacuum gauge showing -0.1 MPa to obtain a PHA dispersion with a solid content of 60%; A PHA dispersion with a solid content of 60% was coated on both sides of the substrate and dried at 145° C. for 201 seconds to form a uniform PHA film layer on both sides of the substrate to obtain a PHA composite film.

[0048] Application Examples Application Example 1 A protective inflatable bubble bag comprises a bag body, wherein a filling cavity is arranged inside the bag body, wherein the bag body is made of a high barrier, waterproof and oil-proof PHA composite film obtained in Example 1, wherein a side containing a PHA layer is located on an inner side of the bag body, an edge of one side of the bag body is overlapped and sealed, and both end edges of the bag body are overlapped and hot-pressed and sealed, wherein the sealing temperature is 180s, the hot-pressing pressure is 60MPa, the hot-pressing time is 1s, and the overlapping width is 2mm.

[0049] Application Example 2-14 The difference between Application Example 2-14 and Application Example 1 is that the sources of the PHA composite membrane are different, as shown in Table 4; Table 4 Sources of PHA composite membranes in application examples 1-14 Application Examples Source of PHA composite membrane Application Example 1 Example 1 Application Example 2 Example 2 Application Example 3 Example 3 Application Example 4 Example 4 Application Example 5 Example 5 Application Example 6 Example 6 Application Example 7 Example 7 Application Example 8 Example 8 Application Example 9 Example 9 Application Example 10 Example 10 Application Example 11 Embodiment 11 Application Example 12 Example 12 Application Example 13 Comparative Example 1 Application Example 14 Comparative Example 2 Application Example 15 A paper cup, comprising a cup body and a cup bottom, both of which are made of paper cup paper, the paper cup paper comprising a paper layer and two layers of PHA composite film, the PHA composite film being a high-barrier, waterproof and oil-proof PHA composite film obtained in Example 2, wherein one side of the two layers of PHA composite film containing the PHA layer is heat-sealed to the two sides of the paper layer respectively to form paper cup paper; the inner surface of the cup body contains the PHA layer, the inner surface of one end face of the cup body is connected to the outer surface of the other end face of the cup body by being rolled and then hot-pressed and sealed, the side of the cup bottom containing the PHA layer is close to the cup body, the outer edge of the cup bottom is provided with a folded edge, and the folded edge is hot-pressed and sealed to the inner surface of the cup body.

[0050] Application Examples 16-27 The difference between Application Examples 16-27 and Application Example 1 is that the sources of the PHA composite membranes are different, as shown in Table 5; Table 5 Sources of PHA composite membranes in application examples 15-27 Application Examples Source of PHA composite membrane Application Example 15 Example 2 Application Example 16 Example 3 Application Example 17 Example 4 Application Example 18 Example 5 Application Example 19 Example 6 Application Example 20 Example 7 Application Example 21 Example 8 Application Example 22 Example 9 Application Example 23 Example 10 Application Example 24 Embodiment 11 Application Example 25 Example 12 Application Example 26 Comparative Example 1 Application Example 27 Comparative Example 2 Performance testing Detection method / test method Test (I) The PHA composite films obtained in Examples 2-12 and Comparative Examples 1-2 were subjected to the following performance tests: Oxygen barrier: The oxygen permeability is calculated by using JIS K7126-1 differential pressure gas permeometer, and the test standard is GB_T 1038-2000.

[0051] Waterproof: According to the national standard GB / T 1540-2002, soak for 30 minutes, and the COBB value is below 5g (COBB is a conventional instrument for testing the water absorption of paper and paperboard surfaces, also known as a paper surface absorption weight tester).

[0052] Oil resistance: refer to GB / T 16929-1997 "Test method for oil permeability of packaging materials" for testing, the test time is 2h, the test temperature is 60℃, observe whether the PHA composite film has oil permeability, the test is conducted twice, and the oils used are a) animal oil and c) vegetable oil in the 5 reagents in the test method.

[0053] Burst resistance: Refer to ISO2758 standard to test the burst resistance.

[0054] The above experiments were carried out 3 times and the average values ​​were taken, as shown in Table 6; Table 6 Experimental data of Examples 2-12 and Comparative Example 1 Combining Example 1 and Comparative Example 1 with Table 6, it can be seen that the oil resistance of Comparative Example 1 is unqualified, the oil resistance of Example 1 is qualified, and the oxygen permeability of Comparative Example 1 is 5.02 cm 3 .mm / (m 2 .24h.atm), while the oxygen permeability of Example 1 is only 2.53cm 3 .mm / (m 2 .24h.atm), and the COBB of Example 1 is smaller than that of Comparative Example 1, and the bursting resistance of Example 1 is 94Kpa greater than that of Comparative Example 1, indicating that the PHA composite film obtained by the production process of the present application has better barrier properties and bursting resistance.

[0055] By comparing Example 5, Example 11, Example 12 and Example 6 and combining with Table 6, it can be seen that the oxygen permeability and COBB of Example 5, Example 11 and Example 12 are greater than those of Example 6, while the burst resistance is smaller than that of Example 6, indicating that the PHA-carboxyl-terminated polycaprolactone, hydrogenated rosin alcohol and plasticizer dispersant of the present application are used to blend and modify PHA, and the obtained PHA-carboxyl-terminated polycaprolactone composite particles are used to produce PHA composite films with better barrier properties and burst resistance.

[0056] Experiment (II) The protective inflatable bubble bag obtained in Application Example 2-14 was subjected to the following performance tests: Compression test: The protective inflatable bubble bag is 20cm long, 10cm wide, and the inflated volume is 1000cm 3 ,Place the protective inflatable bubble bag in the testing machine, start the testing machine, press it down to the surface of the protective inflatable bubble, the pressure is 20N, and the thickness of the protective inflatable bubble bag is measured at this time; the test time is 24h, and the pressure is always maintained at 20N during the process. The test temperature is 25℃ and the humidity is 60%. After the test, the thickness of the bubble bag is measured while maintaining the pressure, and the change rate is calculated. The change rate is equal to the previous thickness divided by the later thickness, multiplied by 100%. The specific data are shown in Table 7.

[0057] Table 7 Experimental data of application examples 2-14 and comparative example 1 Application Examples Rate of change (%) Application Example 2 4.26 Application Example 3 4.18 Application Example 4 3.46 Application Example 5 3.47 Application Example 6 1.83 Application Example 7 1.63 Application Example 8 1.68 Application Example 9 1.29 Application Example 10 1.04 Application Example 11 2.05 Application Example 12 2.89 Application Example 13 19.36 Application Example 14 30.63 It can be seen from Table 7 that the change rate of Application Examples 13-14 is greater than that of Example 2, which indicates that the PHA composite film obtained by the production process of the present application is used in the production of protective inflatable bubble bags, has a better oxygen barrier effect, and reduces the possibility of deformation.

[0058] The rate of change in Application Example 6 is lower than those in Example 5, Application Example 11, and Application Example 12, indicating that the PHA-carboxyl-terminated polycaprolactone, hydrogenated rosin alcohol, and plasticizer dispersant in the present application are blended and modified to obtain PHA-carboxyl-terminated polycaprolactone composite particles for producing PHA composite films having better barrier properties and physical properties. When used in the production of protective inflatable bubble bags, it has better oxygen barrier effect and reduces the possibility of deformation.

[0059] Experiment (III) The paper cups obtained in Application Examples 15-27 were subjected to the following performance tests: Paper cup parameters: water capacity 100mm; cup body edge overlap width 5mm, folded edge overlap width with cup body 5mm.

[0060] Add 100℃ hot water to a paper cup, and place it at 25℃ and 60℃ for 2 hours. During this process, observe whether there is water seepage or leakage on the outside of the paper cup, and record the corresponding phenomenon. Table 8 Experimental data of paper cups obtained from application examples 15-26 Application Examples Phenomenon Application Example 15 No water seepage or leakage Application Example 16 No water seepage or leakage Application Example 17 No water seepage or leakage Application Example 18 No water seepage or leakage Application Example 19 No water seepage or leakage Application Example 20 No water seepage or leakage Application Example 21 No water seepage or leakage Application Example 22 No water seepage or leakage Application Example 23 No water seepage or leakage Application Example 24 No water seepage or leakage Application Example 25 No water seepage or leakage Application Example 26 A small amount of water seeps out from the edge sealing position Application Example 27 A small amount of water seeps out from the edge sealing position It can be seen from the above experiments that a small amount of water seeps out of the edge sealing position in application examples 26-17, while there is no seepage or leakage in application examples 15-25, indicating that the paper cup obtained by using the PHA composite film of the present application has a better barrier effect on water, reduces the phenomenon of seepage and leakage, and improves the practicality of the paper cup.

[0061] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a high barrier, waterproof and oil-proof PHA composite film, characterized in that: The following steps are involved: Dispersing PHA particles in a dispersion liquid to obtain a PHA dispersion having a solid content of 1-3%, and then performing vacuum distillation to obtain a PHA dispersion having a solid content of 60-70%; Applying a PHA dispersion having a solid content of 60-70% on a substrate, and drying at 145-155° C. to form a coating on the substrate; The coating-containing side is hot-pressed at 175-185° C. to obtain a PHA composite film.

2. The method for preparing a high barrier waterproof and oil-proof PHA composite film according to claim 1, characterized in that: The drying time is 35-200s, and the hot pressing pressure is 30-60MPa.

3. The method for preparing a high barrier waterproof and oil-proof PHA composite film according to claim 1, characterized in that: The particle size of the PHA particles is 0.01-5 microns.

4. The method for preparing a high barrier waterproof and oil-proof PHA composite film according to claim 1, characterized in that: The PHA particles are PHA-carboxyl-terminated polycaprolactone complex particles.

5. The method for preparing a high barrier waterproof and oil-proof PHA composite film according to claim 4, characterized in that: The PHA-carboxyl-terminated polycaprolactone composite particles are composed of the following raw materials in percentage by weight: PHA87-93% Carboxyl terminated polycaprolactone 5-10% Hydrogenated Rosin Alcohol 0.2-0.5% The balance is plasticizer and dispersant.

6. The method for preparing a high barrier waterproof and oil-proof PHA composite film according to claim 5, characterized in that: The plasticizer dispersant is epoxidized soybean oil and / or methyl palmitoleate.

7. The method for preparing a high barrier waterproof and oil-proof PHA composite film according to claim 5 or 6, characterized in that: The PHA-carboxyl-terminated polycaprolactone composite particles are prepared by the above method: PHA, carboxyl-terminated polycaprolactone, hydrogenated rosin alcohol, and a plasticizer dispersant were weighed according to weight percentage, heated until all melted, and fully mixed, cooled, and crushed to obtain PHA-carboxyl-terminated polycaprolactone composite particles.

8. A high barrier water and oil proof PHA composite film, characterized by: It comprises a base layer, at least one side of which is provided with a PHA layer. The PHA composite film is obtained by the preparation method of a high-barrier, waterproof and oil-proof PHA composite film according to any one of claims 1 to 7.

9. A protective inflatable bubble bag, comprising a bag body, wherein a filling cavity is provided inside the bag body, and characterized in that: The bag body is made of a high-barrier, waterproof and oil-proof PHA composite film as described in claim 8, the side containing the PHA layer is the inner side of the bag body, one side edge of the bag body is overlapped and sealed, and both end edges of the bag body are overlapped and hot-pressed.

10. A paper cup, comprising a cup body and a cup bottom, wherein both the cup body and the cup bottom are made of paper cup paper, characterized in that: The paper cup paper comprises a paper layer and at least one layer of PHA composite film, wherein the PHA composite film is a high-barrier, waterproof and oil-proof PHA composite film as described in claim 8, wherein one side of the PHA composite film containing the PHA layer is heat-sealed and connected to the paper layer; the inner surface of the cup body contains the PHA layer, and the inner surface of one end face of the cup body is connected to the outer surface of the other end face of the cup body by being rolled and hot-pressed and sealed; the one side of the cup bottom containing the PHA layer is close to the cup body, and the outer edge of the cup bottom is provided with a folded edge, and the folded edge is connected to the inner surface of the cup body by hot-pressing and sealing.

Citation Information

Cited By

  • Coating and hot-pressing process of PHA (Polyhydroxyalkanoate) material

    CN120325497A

  • A coating and hot pressing process for PHA materials

    CN120325497B